1999
DOI: 10.1002/(sici)1097-0231(19990715)13:13<1218::aid-rcm652>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

A laser extraction/combustion technique for in situ δ13C analysis of organic and inorganic materials

Abstract: A CO(2) laser extraction system is described for in situ delta(13)C analysis of organic and inorganic materials. Carbonaceous compounds volatilized by the laser are quantitatively converted to CO(2) gas by a combustion furnace mounted after the sample chamber. Gases produced by the laser and combustion processes are swept by helium carrier gas and separated by a packed gas chromatography column prior to their introduction to an isotope ratio monitoring mass spectrometer. A sample of lentil bean was analyzed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
(7 reference statements)
2
12
0
Order By: Relevance
“…The results presented here highlight the ability of LA-IRMS to spatially pinpoint locations within a microbial mat where labelled substrate accumulates. While this specific LA-IRMS system was previously demonstrated on organic polymers (Moran et al, 2011) and a similar system was demonstrated on plant material (Wieser and Brand, 1999;Schulze et al, 2004;Skomarkova et al, Fig. 3.…”
Section: Resultssupporting
confidence: 57%
“…The results presented here highlight the ability of LA-IRMS to spatially pinpoint locations within a microbial mat where labelled substrate accumulates. While this specific LA-IRMS system was previously demonstrated on organic polymers (Moran et al, 2011) and a similar system was demonstrated on plant material (Wieser and Brand, 1999;Schulze et al, 2004;Skomarkova et al, Fig. 3.…”
Section: Resultssupporting
confidence: 57%
“…Laser micro‐sampling devices also hold potential to ultimately be hybridized with a gas‐accepting AMS system because of their suitability in analyzing intact carbon‐bearing materials at high precision. In the geosciences, such laser systems have been widely used to ablate material into a colloidal suspension of fine particles in a flowing gas for various analyses 2–6. The energy from laser sampling devices also heats surfaces which they contact in addition to ablating the surface; thus simultaneous chemical reaction and/or decomposition is expected.…”
mentioning
confidence: 99%
“…In the geosciences, such laser systems have been widely used to ablate material into a colloidal suspension of fine particles in a flowing gas for various analyses. [2][3][4][5][6] The energy from laser sampling devices also heats surfaces which they contact in addition to ablating the surface; thus simultaneous chemical reaction and/or decomposition is expected. As a result, similar types of lasers (neodymium-doped yttrium aluminum garnet, or Nd-YAG) have been used on similar types of substrates (calcium carbonate) to analyze both ablated particles by inductively coupled plasma mass spectrometry (ICP-MS) 2,4,7 and evolved CO 2 (from decomposition of CaCO 3 (s) to CaO (s) and CO 2 (g)) gas using gas-sourced isotope ratio mass spectrometry (ir-MS).…”
mentioning
confidence: 99%